Design and Construction of a Fish Seed Counting Tool Using Infrared Proximity Sensors Based on PLC and HMI - Erawadi, Dedi; Berlianti, Rahmi; Hendra; Vitto Andrivanly; Kusuma, Yuda Perdana (Universitas Negeri Padang, 2024)
Fish hatcheries are a significant endeavor in aquaculture with promising economic potential. However, the manual process of counting fish seeds is time-consuming and inefficient. This paper examines a prototype of a fish seed counting device based on a Programmable Logic Controller (PLC) and Human Machine Interface (HMI) that can expedite the counting process. The device is designed using infrared proximity sensors, a DC power window motor, a solenoid valve, and is controlled by a PLC and HMI. The infrared proximity sensor is placed under the fish passageway to detect fish presence. The counting results are displayed on the HMI screen. After counting, the DC motor closes the fish passageway, and the fish in the plastic packaging are automatically tied for oxygen filling. Testing results indicate that this fish seed counting device functions well and can improve the efficiency of the fish seed counting process